Analisis Risiko Pergudangan Menggunakan Metode Hazard Identification Risk Assessment and Risk Control (HIRARC) di Perusahaan Pengeboran Minyak dan Gas - Vikaliana, Resista; Melani, Windy (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
PT Pertamina EP Field subang is part of Pertamina EP which is located in zone 7 regional 2 and is engaged in oil and gas drilling. The production area is spread across Subang and Karawang districts. Pertamina EP Field subang has a division tasked with Supporting all workers' needs, including the need for tools, materials and services, namely the Supply Chain Management (SCM) division. The HIRARC document for the SCM warehouse area does not describe risks based on the actual conditions of the warehouse because the creation of the HIRARC document was carried out before the warehouse was operational so that this situation could influence the risk of work accidents being greater. The aim of this research is to analyze risk by identifying and assessing risks and providing recommendations for appropriate risk control. The method used in this research is the Hazard Identification Risk Assessment and Risk Control (HIRARC) method. HIRARC is a method that aims to minimize the occurrence of accidents in the work area by identifying, assessing and controlling risks. Risk assessment by determining the rating of severity (S) and Probability (P) of potential hazards on each risk obtained in the previous stage carried out by the appropriate experts in this study. Then based on the risk assessment at the general warehouse, the results were obtained that 2 high-risk activities and 6 medium-risk activities were obtained. In the chemical warehouse, it was obtained that there were 1 high-risk chemical material, 5 medium-risk activities and 3 low-risk activities. In the yard warehouse, 3 high-risk activities, 1 medium-risk activity and 1 low-risk activity were obtained. For control recommendations that companies can do to minimize the occurrence of high risks, namely carrying out administrative control in the form of adding safety signs in the loading unloading area of the warehouse yard, making forklift lines, and adding PPE storage areas in the chemical warehouse area.